Improving the effectiveness of the international law of human trafficking: a vision for the future of the US trafficking in persons reports - Gallagher, Anne T. (Human rights review, 2011)
n 2000, the United States Congress passed the Victims of Trafficking and Violence Protection Act requiring its State Department to issue annual Trafficking in Persons Reports (TIP Reports) describing “the nature and extent of severe forms of trafficking in persons” and assessing governmental efforts across the world to combat such trafficking against criteria established by US law. This article examines the opportunities and risks presented by the TIP Reports, tracing their evolution over the past decade and considering their impact on the behavior of states. In looking to the future, the article focuses on how this influential unilateral compliance mechanism could improve its legitimacy, respond to negative impacts, and better contribute to the international legal regime around trafficking.